Oncologic safety of nipple-sparing mastectomy in patients with short tumor-nipple distance - Balcı, Fatih Levent; Kara, Halil; Dülgeroğlu, Onur; Uras, Cihan (Blackwell Publishing Inc., 2019)
Background: There is a tendency to avoid nipple-sparing mastectomy (NSM) when a tumor-nipple distance (TND) is <2 cm due to the risk of occult nipple involvement. The purpose of the study was to determine whether the patients who undergo NSM with immediate reconstruction are oncologically safe when TND is <2 cm. Methods: Patients who underwent NSM followed by immediate reconstruction for breast cancer were retrospectively analyzed. Patients who are negative for nipple-base in either frozen-section or paraffin histopathology were included. MRI was used to obtain TNDs to compare local-recurrence-free and disease-free survival in group I (TND <2 cm) and group II (TND ?2 cm). Disease-free survival rates were determined to assess the outcome. Results: Of the 214 cases with malignancy on MRI, 21 cases diagnosed with pure ductal carcinoma in situ were excluded. Among the 193 NSM cases diagnosed with invasive cancer, TND was <2.0 cm in 59 (30.56%) cases and ?2.0 cm in 134 (69.43%) cases. No significant differences were found between groups in regards to ER, PR, HER2-neu status, and nodal involvement (P = 0.34, P = 0.41, P = 0.54, and P = 0.12 respectively). In a median follow-up time of 62 months (range; 13-114), patients in group I had four local recurrences, whereas group II was found to have five local and three distant metastases. No significant differences were observed between groups concerning disease-free survival (10-year DFS 93.2% vs 96.3%; P = 0.368 respectively). Conclusions: Patients who have invasive cancer diagnosis with a TND <2 cm are eligible to undergo therapeutic NSM with immediate reconstruction.
Keywords: Breast Cancer; Mastectomy; Nipple-Sparing Mastectomy